HOME OR HOSPITAL FOR PEOPLE WITH DEMENTIA AND ONE OR MORE OTHER MULTIMORBIDITIES: WHAT IS THE POTENTIAL TO REDUCE AVOIDABLE EMERGENCY ADMISSIONS?. Issue 9 (18th August 2016) - Voss, Sarah; Benger, Jonathan; Black, Sarah; Brandling, Janet; Buswell, Marina; Cheston, Richard; Kirby, Kim; Purdy, Sarah
Abstract : Older people with multiple health problems often call a 999 ambulance. Where one of these health problems is dementia, the risk of ambulance use, A&E attendance and hospital admission are all increased. It is important to try and reduce this, as patients with dementia tend to have poor outcomes when they are taken to A&E or admitted to hospital unnecessarily. This study aims to find out why older people with multiple health issues including dementia are taken to hospital by ambulance, instead of being treated in the community. This will build on earlier work to find the true burden of dementia on pre-hospital care. It will look at the length of time paramedics spend at the scene, factors guiding the decision to transport and alternatives to A&E visits and hospital admissions. There will be 3 phases of work: Phase 1: Analysis of existing ambulance service data from previous 999 calls. Phase 2: Observations of ambulance call-outs to patients with multiple health problems including dementia. Phase 3: An assessment of what could be provided in the community to avoid hospital admission. This proposal is part of an overall research plan, and will inform further investigations and future service delivery. We plan to study issues specific to the ambulance service that reduce or increase the risk of someone with dementia and other long-term health conditions requiring hospital care, rather than being looked after in or close to their own home. It contributes to a larger piece of work developing and evaluating safe and effective alternatives to hospital admission for people with dementia. This will lead to a reduction in the number of avoidable emergency admissions, and better patient outcomes, for example through the introduction of rapid response health and social care teams as described in the NHS Five Year Forward View (2014).